Integrating Halal Assurance and Quality Management: A Strategic Framework for Sustainable Growth in the Food Industry - Hidayati, Luki; Sucipto, Sucipto; Juliana, Juliana; Cheumar, Muhammadtahir (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2024)
AbstractThe rising demand for halal-certified food products necessitates a robust assurance system that ensures compliance with religious standards while maintaining food quality and safety. Integrating the Halal Assurance System (HAS) with the Quality Management System (QMS) enhances efficiency but faces challenges such as certification discrepancies, operational constraints, and regulatory complexities. This study employs a systematic literature review using the PRISMA framework, analyzing journals from Scopus, ScienceDirect, and Web of Science. Findings indicate that differences in halal certification standards, including JAKIM (Malaysia), BPJPH (Indonesia), and GSO (Gulf), hinder HAS-QMS harmonization. Small and medium-sized enterprises (SMEs) struggle with implementation due to resource limitations and insufficient training. Technologies like blockchain and the Internet of Things (IoT) improve supply chain transparency and audit efficiency. This study emphasizes integrating halal standards with risk-based quality management, regulatory harmonization, and technological advancements to enhance HAS-QMS adoption. The  implications  of  the  research can  be  utilized  by  regulators,  industry,  and academics  in  designing  more  effective  policies  and  strategies  to  implement  the  integration  of  halal  assurance systems and quality management systems.Keywords: halal assurance system, halal certification, quality management system, risk management, system integration        AbstrakPeningkatan permintaan produk pangan bersertifikat halal menuntut sistem jaminan yang memastikan kepatuhan terhadap standar keagamaan serta kualitas dan keamanan pangan. Integrasi Sistem Jaminan Halal (SJH) dengan Sistem Manajemen Mutu (SMM) meningkatkan efisiensi industri pangan tetapi menghadapi tantangan seperti perbedaan standar sertifikasi, kendala operasional, dan kompleksitas regulasi. Studi ini menggunakan metode systematic literature review dengan kerangka PRISMA untuk menganalisis literatur dari jurnal bereputasi yang terindeks di Scopus, ScienceDirect, dan Web of Science. Hasil studi mengidentifikasi bahwa perbedaan standar halal di berbagai negara, seperti JAKIM (Malaysia), BPJPH (Indonesia), dan GSO (Gulf), menjadi hambatan utama dalam harmonisasi SJH-SMM. Usaha kecil dan menengah (UKM) mengalami kesulitan dalam implementasi akibat keterbatasan sumber daya dan pelatihan. Adopsi teknologi seperti blockchain dan Internet of Things (IoT) dapat meningkatkan transparansi rantai pasok halal serta efektivitas sistem audit. Studi ini menekankan pentingnya integrasi standar halal dengan manajemen mutu berbasis risiko, harmonisasi regulasi, dukungan teknologi, dan peningkatan kapasitas industri untuk mempercepat adopsi SJH-SMM. Implikasi  hasil penelitian dapat dimanfaatkan oleh regulator, industri, dan akademisi dalam merancang kebijakan serta strategi yang lebih efektif untuk mengimplementasikan  integrasi sistem jaminan halal  dan sistem manajemen mutu.Kata kunci: integrasi sistem, manajemen risiko, sertifikasi halal, sistem jaminan halal, sistem manajemen mutu